2023
DOI: 10.1037/tra0001428
|View full text |Cite
|
Sign up to set email alerts
|

Shame-induced dissociation: An experimental study of experiential avoidance.

Abstract: Objective: The study experimentally investigated shame-induced dissociation, and to what extent that process was associated with exposure to childhood maltreatment. Method: Using a shame-related script-driven imagery paradigm and mirror-viewing task, 50 female participants from the community recalled two shamerelated and two neutral autobiographical memories, after which they listened to recordings of themselves retelling the narratives looking in a mirror or at a black curtain (i.e., mirror-viewing task). Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Evidence for dissociative and social pathways in psychosis (Heriot-Maitland, Wykes, & Peters, 2021) and for the traumatic/dissociative properties of shame (Dorahy et al, 2017;Kouri, D'Andrea, Brown, & Siegle, 2023;Matos & Pinto-Gouveia, 2010) supports a theoretical framework in which shame, a 'threat to social self', could influence dissociative processes as a potential causal mechanism for psychosis symptoms. In line with social rank theory (Gilbert, 1992), shame is considered to be a negative social ranking experience that threatens human survival needs for acceptance and connection.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Evidence for dissociative and social pathways in psychosis (Heriot-Maitland, Wykes, & Peters, 2021) and for the traumatic/dissociative properties of shame (Dorahy et al, 2017;Kouri, D'Andrea, Brown, & Siegle, 2023;Matos & Pinto-Gouveia, 2010) supports a theoretical framework in which shame, a 'threat to social self', could influence dissociative processes as a potential causal mechanism for psychosis symptoms. In line with social rank theory (Gilbert, 1992), shame is considered to be a negative social ranking experience that threatens human survival needs for acceptance and connection.…”
mentioning
confidence: 79%
“…Like trauma memories, shame experiences and memories may be highly threatening to an individual, particularly in relation to their social position (rank) and inclusion, triggering dissociative processes to avoid or regulate these overwhelming feelings. In an experimental study, Kouri et al (2023) found that shame-related memories generated dissociative state responses, and that the degree of people's dissociation was moderated by their level of experiential avoidance (conscious attempts to avoid the feeling of shame). This supports the idea that dissociative states may function as a strategy to protect against feelings of shame.…”
mentioning
confidence: 99%
“…An exciting new development in the literature – with real potential in guiding our future understanding of psychosis – is the research into the dissociative properties of shame (Dorahy et al, 2017; Kouri et al, 2023). If shame is indeed dissociative, as these studies suggest, then shame could be a prime candidate for future research into the pathways of causation/maintenance of psychosis (Heriot‐Maitland et al, 2021).…”
Section: Evidence That Supports the Processes Targeted In Cft For Psy...mentioning
confidence: 99%